ML098 enhances intracellular bacterial clearance in bladder epithelial cells by activating Rab7 and promoting lysosomal biogenesis - Yin, Hao; Zhu, Jiaoli; Yin, Jiamin; Xue, Yi; Wang, Xin (Bangladesh Journal of Pharmacology, 2025)
The aim of this study was to investigate the effect of ML098 on the intra-cellular bacterial count of bladder epithelial cells infected with uropathogenic Escherichia coli. The number of intracellular bacteria were counted after cell lysis present in coated Luria-Bertani agar plates. Lysotracker red was used to detect the numbers of lysosomes in cells. The expression of lysosome associated membrane protein 1 within cells was detected by western blot and q-PCR methods. Rab7 pulldown activation assay was used to detect the expression of intracellular active Rab7. The results showed that ML098 (1 µM) could reduce the number of intracellular bacteria in bladder epithelial cells 6 hours after E. coli infection (p<0.05), increased the number of lysosomes in cells (p<0.05), and increased the expression of intracellular active Rab7 (p<0.05). Therefore, ML098 can promote intracellular bacterial clearance, possibly by increasing the expression of active Rab7 in cells, thereby increasing the number of lysosomes in bladder epithelial cells.